Adsorption of Brilliant Green Dye on Biochar Prepared From Lignocellulosic Bioethanol Plant Waste. Issue 1 (17th November 2015) - Saif Ur Rehman, Muhammad; Kim, Ilgook; Rashid, Naim; Adeel Umer, Malik; Sajid, Muhammad; Han, Jong‐In
Abstract : This study was aimed at the adsorption of Brilliant Green (BG) on hydrolyzed rice straw biochar, which was obtained from a lignocellulosic bioethanol process. Rice straw biochar (RBC) possessed surface properties such as a Brunauer–Emmett–Teller (BET) surface area of 232.31 m 2 /g, a total pore volume of 0.30 cm 3 /g, and an average pore width of 5.22 nm. Adsorption studies were carried out to investigate the effect of experimental factors such as pH (2–10), biochar dose (0.05–1.25 g/L), contact time (30–480 min), and temperature (30 to −50°C) on the adsorption of BG. The Langmuir isotherm ( R 2  = 0.998) fitted well to the adsorption data for initial dye concentrations of 20–500 mg/L, implying that BG adsorption occurred in the form of a monolayer on RBC. Adsorption kinetics was well fitted by the pseudo‐second order kinetic model ( R 2  ≥ 0.988) for all tested dye concentrations. The thermodynamic study revealed that BG adsorption on RBC was spontaneous, favorable, and a physical process. The maximum adsorption capacity of RBC was found to be 111.11 mg/g. These results showed that RBC, prepared from the waste of the bioethanol process, can be effectively used as a promising cheap adsorbent to remove dyes from aqueous solution. This approach of product diversification (bioethanol along with biochar) may lead to a cost effective and cleaner production of bioethanol. Abstract : Rice biochar (RBC), prepared from ultrasound‐sulfuric acid hydrolyzed rice straw, possesses good characteristics as an adsorbent for dyes. The results showed that each g of RBC could remove 111.11 mg of dye from aqueous solution. This approach ensures the practical application of cleaner production of bioethanol from rice straw as well as process integration in terms of wastewater treatment.